DEVELOPMENT AND VALIDATION OF A SCALE TO ASSESS URBANITES’ PERCEPTION TOWARDS URBAN AGRICULTURE - Cortes, Sylvester T (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
There is a limited instrument that assesses urbanites’ perceptions towards urban agriculture. Thus, the present study aimed to develop a valid and reliable scale to examine perception towards urban agriculture (UA). This scale aimed to eventually help in evidenced-based program and policy-making regarding UA. To do so, a scale called Perception Towards Urban Agriculture (PTUA) was developed according to the constructs proposed by Surls et al. (2014) on impacts of UA, namely: social, health, and economic. Environmental and aesthetic values are added as one construct as suggested by the literature review. The validity and reliability of the scale were established by examining 509 responses from Cebu City, Philippines. Exploratory factor analysis was performed and confirmed the hypothesized four-structure model of which the percentage of variance explained by the scale is 83.849. The model was further analyzed using the confirmatory factor analysis method through the Maximum Likelihood approach. Three model fit indices recorded satisfactory results (CFI = 0.962; NNFI = 0.959; RMSEA = 0.062), thus, further supporting the four-factor scale. The other analyses, such as convergent validity, concurrent validity, and reliability, also provide further evidence of the scale’s validity. There may be an issue with respect to scale’s discriminant validity, but the conceptual distinction of each factor is the ultimate purpose of retaining the factors or items. In conclusion, PTUA scale is a valid and reliable tool to evaluate urbanites’ perceptions towards UA as input for introducing UA programs and policies.